The taxonomy of metacognition - Tarricone, Pina. (Hove : New York : Psychology Press, 2011)
Metacognition is a complex construct which is fundamental to learning. Its complex, fuzzy and multifaceted nature has often led to its colloquial application in research, resulting in studies that fail to identify its theoretical foundation or elements. In response to this, the research community continues to call for a comprehensive understanding of the construct of metacognition. This book is a response to this
Includes bibliographical references and index.
Keywords: Metacognition; Cognition; Memory